PEMBELAJARAN BERNYANYI LAGU WAJIB NASIONAL DENGAN MODEL PEMBELAJARAN LANGSUNG DI SEKOLAH DASAR - Mansurdin Mansurdin (Universitas Negeri Padang, 2017)
This research is a collaboration between faculty and students, with the aim of generating a synergy in the final work. The purpose of this study was to increase student’s ability to sing national anthems with direct teaching on 4th grade of SDN 01 Bandar Buat Padang. This study uses qualitative and quantitative approach to the type of research is the Classroom Action Research (PTK ). The results showed the increase of student’s ability to sing outcomes in the first cycle is obtained an average of 74,6 % , while in the second cycle gained an average of 87,6 %.Keywords: Singing Skills; Direct Learning Model